DINAMIKA SOSIAL BUDAYA TRADISI TURUN MANDI DI KENAGARIAN TAEH BARUAH KECAMATAN PAYAKUMBUH - Fitri, Reno Aidil; Umar, Iswandi (JURNAL BUANA, 2024)
This study discusses the socio-cultural dynamics of the bathing tradition in Kenagarian Taeh Baruah, Payakumbuh District. The aims of the study were to find out: 1) The values ​​contained in the tradition of taking a bath in the Taeh Baruah district, Payakumbuh sub-district, 2) The driving factors for social change in the tradition of taking a bath in Kenagarian Taeh Baruah, Payakumbuh District. This type of research is ethnography with qualitative research methods. informants in this study were traditional and community leaders in Kenagarian Taeh Baruah withuse snowball sampling technique. Data collection techniques used are through observation, interviews and documentation. Data analysis techniques include data collection, data reduction, data presentation/display and drawing conclusions. The results of this study concluded: 1) The values ​​contained in the Mandir Drop Tradition in Taeh Baruah Village, namely Religious or Religious Values, Hospitality Values, Mutual Cooperation Values, Caring Values, Cultural Values. 2) The factors that cause changes in the tradition of bathing down in Kenagarian Taeh Baruah are factors that come from within, namely the existence of new discoveries, the existence of ignorance or not understanding the community about the tradition of bathing down. and Factors originating from outside, namely the condition of the physical environment and the influence of other community cultures.